Analisa Aerodinamika Pada Bodi Mobil Bayu Surya Menggunakan Cfd Pada Software Ansys 15.0 - Huda, Nurul (2016)
One reference to the development of a car is in the shape of the body. An aerodynamic body shape reduces aerodynamic prisoners so as to optimize the engine power to be thrust traction vehicles, fuel-efficient and maintain vehicle stability. Thesis research aims to determine the role of design changes to the characteristics of the flow patterns and the value of the aerodynamic drag coefficient on the car body prototype BAYU SURYA. This research was conducted in two stages modifications, first by changing the geometry of the corner of the glass hood with existing car body at an angle of 150O, 160O and 170O become later by changing the shape of the leading edge of the initially flat into concave and convex. Design of car body manufacture using SolidWorks 2014 software and simulated using CFD in ANSYS 15.0 software with the boundary grid mesh 90 mm and 45 mm body grid mesh, the inlet velocity of 11.11 m / s and conditions assumed domain like a real situation. CFD simulation results obtained from a streamlined visualization, vector velocity, pressure contours and value style of prisoners in each body design. At first modification prisoners style value decreases with increasing angle hood with glass 150O, 160O, and 170O. then the second modification changes the shape of the leading edge has a convex shape variation smaller than that prisoners style variations flat and concave shapes.